Product Lifecycle Management (Volume 3): The Executive Summary - Stark, John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This third volume provides an executive overview of Product Lifecycle Management (PLM), and details the roles that executives play in PLM initiatives. This book also explains why PLM emerged, why it is so important, the principles of PLM strategy, and the typical steps in a PLM initiative. Throughout the book, the author presents examples and cases studies, demonstrating the various roles of executives in PLM initiatives. The coverage is informed by John Stark's experience of working with companies on more than 100 PLM initiatives. The present book broadens the reader's understanding of PLM, nurturing the skills needed to implement PLM successfully and to achieve world-class product performance across the product lifecycle. The book provides the executive reader with a thorough explanation of PLM, and the required knowledge to lead or participate in a PLM Initiative.
Introduction to the Executive Summary -- My Experience with PLM -- What's PLM? What's a PLM Initiative? -- Seven Parameters of the PLM Paradigm -- The Benefits of PLM, Another Why PLM? -- Twelve Principles of PLM Strategy -- Steps in a PLM Initiative -- Executive Roles in PLM Initiatives.
Keywords: Industrial Management; Project management; Engineering design; Operations research; Technological innovations; Strategic planning; Leadership; Industrial Management; Project Management; Engineering Design; Operations Research and Decision Theory; Innovation and Technology Management; Business Strategy and Leadership